Aplikasi Ilmu Matematika Dalam Memahami Konsep Persamaan Reaksi Kimia - Lidyawati Lidyawati; Bukhari Bukhari; Muhammad Muhammad (Center for Research and Community Service (LPPM) University of Abulyatama, 2018)
The equation of chemical reactions can be synchronized in several ways, including the mathematical equation of chemical reactions. In an equivalent chemical reaction, the relationship of any amount of product and reactant usually forms a ratio of a round number. An understanding of the chemical reaction equation is needed to understand the stoichiometric material, since stoichiometry is the basic material that must be well understood as the foundation for the understanding of subsequent chemicals. Stoichiometry can be used to calculate the amount of product that can be produced from a given number of reactants..